HUBUNGAN FAKTOR KESEHATAN LINGKUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS GUNUNGSITOLI IDANOI TAHUN 2024 - Mendrofa, Debora; Dachi, Rahmat Alyakin (TOUR HEALTH JOURNAL, 2024)
Background: The environmental conditions in the homes of toddlers suffering from diarrhea show that most of the clean water facilities do not meet health requirements, for example they are not protected from sources of pollution. Likewise, most of the latrine facilities do not have waterproof floors, are slippery, and flow directly into the river. Waste management is still far from health requirements and most rubbish bins do not have covers, there is no separation of organic and inorganic waste. Household waste water drainage channels are still close to the house, which creates a breeding ground for vectors that can carry disease. Purpose: The aim of this research is to analyze the relationship between clean water facilities, latrine facilities, waste management, waste water drainage management and the incidence of diarrhea in the work area of the UPTD Puskesmas Gunungsitoli Idanoi District. Method: The type of research is quantitative and cross sectional research, researchers analyzed data from 4,485 families, obtained through questionnaire and observation methods, data were analyzed using the chisquare test with a confidence level of 95%. Disscusion and Conclusion: Results through statistical tests showed that all variables were related to the incidence of diarrhea in toddlers in the UPTD work area of the Gunungsitoli Idanoi District Health Center.All variables studied are related to the incidence of diarrhea, so various efforts need to be madethe role of the community and health workers in improving the quality of a healthy environmentwhich is related to the incidence of diarrhea in the UPTD work area of the Gunungsitoli Idanoi District Health Center.